Consent for genetic investigations in the community paediatric setting: a snapshot of current practice. (24th May 2012) - Burke, K; Brooks, J
Abstract : Genetic investigations form part of the first line investigations for common presentations in the community setting, most notable, global developmental delay and autistic spectrum disorders. Issues around informed consent for genetic investigations are complex: results may not be interpretable without parental samples, may reveal misattributed parentage and may have consequences for further childbearing. Samples are commonly stored for analysis at a later date, should further clinical information or technological advancement have the potential to offer further information about a potential diagnosis. The Royal College of Physicians, in partnership with the Royal College of Pathologists and the British Society for Human Genetics have issues new guidance about consent for genetic investigations (September, 2011). The retrospective notes audit compared current practice with the suggested guidance for informed consent, and the documentation of these decisions in the clinical notes. The notes of 36 children who had undergone genetic investigations were examined. None of these notes recorded evidence of informed consent having been sought during consultations. There was no evidence to suggest that parents had been informed about sample storage, or the potential need for matched 'trio' samples, should a variation be identified. There is a need to ensure informed consent is taken and accurately documented in the clinical notes. In some regions and clinical areas, standardised consent forms provide a format to lead the clinician and consenting parent/carer through this process. Identifying the facets of informed consent for parents and carers would enable paediatrician practicing in the community setting to take consent in a comprehensive and ethically robust way.